Kleptomania: Manifestasi Klinis dan Pilihan Terapi - Levani, Yelvi; Prastya, Aldo Dwi; Ramadhani, Safira Nur (MAGNA MEDICA Berkala Ilmiah Kedokteran dan Kesehatan, 2019)
Kleptomania: Clinical Manifestations and Treatment OptionsKleptomania (pathological stealing) is a form of mental disorder characterized by repeated stealing. This behavior is accompanied by a strong desire that is difficult to control. Kleptomania can be associated with psychiatric disorders such as depression, alcoholism, anxiety disorders and obsessive compulsive disorder. Kleptomania has symptoms in common with addiction such as strong pressure before the desire is achieved, decreased desire immediately after the action is carried out, there is a time lag (hours, days or weeks) for the emergence of the desire to commit repeated theft, and there is a feeling of pleasure after doing the action Kleptomania It can also be related to mood changes. Diagnostic criteria for kleptomania based on the American Psychiatric Association Diagnostic and Statistical Manual of Mental Disorders include the behavior of stealing items repeatedly where the patient is unable to control the desire. Stolen items are usually not needed by the patient and are not for sale. There are several tools for establishing the diagnosis of kleptomania, including the Yale Brown Obsessive Compulsive Scale Modified for Kleptomania (K-YBOCS) and the Kleptomania Symptom Assessment Scale (K-SAS). K-YBOSC is a tool to measure the severity of kleptomania symptoms. For pharmacological therapy, including Selective serotonin reuptake inhibitors (SSRI) which is a class of antidepressants that work by increasing serotonin levels in the brain and naltrexone is a medical therapy for alcohol addiction. , systemic desensitization and aversion therapy. This psychotherapy aims to change the sufferer's perception of the act of stealing and divert interest to other things. Kleptomania (curi patologis) merupakan salah satu bentuk gangguan kejiawaan yang ditandai dengan mencuri berulang. Perilaku tersebut disertai dengan keinginan kuat yang sulit dikendalikan. Kleptomania dapat berhubungan dengan gangguan kejiwaan seperti depresi, kecanduan alcohol, gangguan kecemasan dan gangguan obsesif kompulsif. Kleptomania memiliki kesamaan gejala dengan adiksi seperti adanya tekanan yang kuat sebelum keinginan tersebut dicapai, penurunan keinginan segera sesaat setelah aksi dilakukan, adanya jeda waktu (jam, hari atau minggu) terhadap munculnya keinginan melakukan aksi pencurian berulang, serta terdapat perasaan senang setelah melakukan aksinya Kleptomania juga dapat berkaitan dengan perubahan mood. Kriteria diagnostik untuk kleptomania berdasarkan American Psychiatric Association Diagnostic and Statistical Manual of Mental Disorders diantaranya adalah prilaku mencuri barang berulang dimana penderita tidak mampu untuk mengendalikan keinginan tersebut. Barang yang dicuri biasanya tidak diperlukan oleh pasien dan bukan untuk dijual. Terdapat beberapa alat bantu untuk penegakkan diagnosis kleptomania diantaranya adalah Yale Brown Obsessive Compulsive Scale Modified for Kleptomania (K-YBOCS) dan Kleptomania Symptom Asessment Scale (K-SAS). K-YBOSC merupakan alat ukur keparahan gejala kleptomania. Untuk terapi farmakologi diantaranya Selective serotonin reuptake inhibitors (SSRI) merupakan golongan antidepresan yang bekerja dengan meningkatkan level serotonin di otak dan naltrexon merupakan terapi medikasi terhadap adiksi alcohol selain itu beberapa psikoterapi yang banyak dilakukan untuk penderita kleptomania adalah Cognitive Behavioral Therapy (CBT), psikoterapi kognitif, desensitisasi sistemik dan terapi aversi. Psikoterapi ini bertujuan untuk mengubah persepsi penderita terhadap tindakan mencuri dan mengalihkan minat ke hal lain.